High Prevalence of Oncogenic Human Papillomavirus Types 16/18 in Negative Inflammatory Pap Smears Implies Masking Cervical Cancer - Ali, Mohammad; Kumar, Pankaj; Gulfishan, Syed; Sinha, Shweta; Kumar, Sachin; Kumar, Manishankar; Sinha, Priti Lata; Prakash, Aman; Singh, Kritika; Singh, Manisha; et al. (Archives of Clinical and Biomedical Research, 2024)
Purpose: Infection of high-risk HPV types 16/18 have been known to be the principal causative agents for the development of cervical cancer. The objective of the present study was to examine whether positive oncogenic HPV types 16/18 in a negative inflammatory Pap smear could be an indicator of cervical cancer risk in a symptomatic woman. Methods: A total of 550 symptomatic women who attended the gynaecology outpatient department of the Mahavir Cancer Sansthan, Patna, for pap smear examinations were screened, and simultaneously cervical scrapes were taken for HPV DNA analysis. After evaluation of Pap smear reporting, an oncogenic HPV types 16/18 test using qRT PCR was conducted through preserved DNA, on 431 women with negative inflammatory smears and 75 women without inflammation negative Pap smears. A further 82 HPV positive women with negative inflammatory smears were randomly selected due to their highly clinical symptoms from the study population for colposcopy guided biopsy to correlate HPV positivity with negative inflammatory smears. Results: The prevalence of oncogenic HPV types 16/18 positive cases in 431 with inflammatory smears was found to be 389. However, HPV type 18 was detected only in 7 women whereas in 21 out of 75 women without inflammatory negative smears, only HPV type 16 was detected. The association with HPV positivity was found to be statistically highly significant (p<0.0001). A biopsy of 82 patients revealed that 24 (29%) women had cervical cancer, of which 19 had a Squamous cell carcinoma and 05 had Adenocarcinoma, 20 women had cervicitis, 02 women had a dysplasia, 12 women had a benign tissue, 12 women had a haemorrhage, and 06 women were asked to repeat biopsy. Conclusion: Thus, detection of high-risk HPV can be utilized to eliminate false negative Pap tests, especially in those with inflammation, as inflammatory smears have a greater risk of developing neoplasia.